Rancang Bangun Die Set sebagai Alat Bantu Press Tool untuk Proses V-Bending Stainless Steel - Nur, Rusdi; Suyuti, Muhammad Arsyad; Iswar, Muhammad (Jurnal Energi Dan Manufaktur; Vol 14 No 1 (2021)DO - 10.24843/JEM.2021.v14.i01.p04, 2022)
Press tools, as production aids, are widely used in the manufacturing industry for metal forming, including the bending of plate materials. The press tool consists of a die set used to cut or shape a product or component from sheet metal by using a press machine as a pressing tool that can produce products with uniform quality and in a short time. The stages in the die set design process consist of several stages, namely: 1) the design stage is carried out using Autodesk Fusion 360 software, 2) the manufacturing stage is carried out using machine tools and their accessories, 3) the assembly stage of each component both made and standard become a complete stu die set, 4) the stage of testing the die set by performing a compression test on a compression testing machine (UTM Galdabini) with various test parameters. The results of the buckling test show that the bending force required for bending a stainless steel plate with a thickness of 1 mm is in the range of 92 N – 125 N, while for a thickness of 2 mm it ranges from 113 N – 163 N. The bending angle produced is 107 O 45' – 115 O 45' for a thickness of 1 mm, and 100 O 20' – ??116 O 45' for a thickness of 2 mm. The conclusion obtained is that this die set designed and made has shown performance and meets the requirements as a press tool that can bend stainless steel plates.